THE ROLE OF PARENTS TO CHILDREN IN LEARNING ENGLISH - Ferbiano Souhucken; Nihta Liando; Paula Rombepajung (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The aims of this research was to find out the role of parents to children in learning English. This study was conducted by using descriptive qualitative method. The data of this research were questionnares . After analyzed the data, the result of this study are follows several theories associated with parents as the supporter and motivator. Based on the result of the research that has been conducted on “The Role of Parents to Children in learning English”,it can be conducted that the role of parents as a supporter and motivator is very important based on the data that has been collected,there are 100% of parents wants to participate in supporting and motivating their children in learning,especially learning English